Statistical Analysis of Price Behaviour of Pearl millet in Rajasthan : Price Behaviour of Pearl millet - SUMAN CHAUDHARY; Sharma, Madhu; Prakash, Om; Pawariya, Vikash (Annals of Arid Zone, 2023)
In view of this the present study was undertaken by collecting monthly wholesale prices of pearl millet in Rajasthan. This study was based on the secondary data on arrival and prices of pearl millet in selected A.P.M.Cs., of Rajasthan for the period of 11 years i.e., from 2010-11 up to 2020-21. In the analysis it was revealed that there was an increasing trend in the prices of pearl millet in the all selected mandies. Yearly price of pearl millet in all selected mandies, there was not a clear cyclical movement visible. It is evident from the results that the irregular fluctuations did not exhibit any definite periodicity in their recurrence. There was similarity in seasonality of prices in Alwar and Barmer mandies but there were difference and much variations in prices of pearl millet over months in Jaipur mandi. It was observed that pearl millet arrival pattern was almost similar in all selected mandies which was higher just after the harvesting and lower during lean period. Looking to IPR and ASPV, there was much variability in prices in Barmer mandi while coefficient of variation was highest in Jaipur mandi.